Cancer-linked targets modulated by curcumin - Noor Hasima, N.; Aggarwal Bharat, B. (2012)
In spite of major advances in oncology, the World Health Organization predicts that cancer incidence will double within the next two decades. Although it is well understood that cancer is a hyperproliferative disorder mediated through dysregulation of multiple cell signaling pathways, most cancer drug development remains focused on modulation of specific targets, mostly one at a time, with agents referred to as "targeted therapies," "smart drugs," or "magic bullets." How many cancer targets there are is not known, and how many targets must be attacked to control cancer growth is not well understood. Although more than 90 of cancer-linked deaths are due to metastasis of the tumor to vital organs, most drug targeting is focused on killing the primary tumor. Besides lacking specificity, the targeted drugs induce toxicity and side effects that sometimes are greater problems than the disease itself. Furthermore, the cost of some of these drugs is so high that most people cannot afford them. The present report describes the potential anticancer properties of curcumin, a component of the Indian spice turmeric (Curcuma longa), known for its safety and low cost. Curcumin can selectively modulate multiple cell signaling pathways linked to inflammation and to survival, growth, invasion, angiogenesis, and metastasis of cancer cells. More clinical trials of curcumin are needed to prove its usefulness in the cancer setting.